Soluble urokinase‐type plasminogen activator receptor (suPAR) and interleukin‐6 levels in hyperemesis gravidarum. Issue 9 (September 2018) - Desdicioglu, Raziye; Yildirim, Melahat; Kocaoglu, Gulcan; Cendek, Busra Demir; Avcioglu, Gamze; Tas, Emre Erdem; Sengul, Ozlem; Erel, Ozcan; Yavuz, Ayse Filiz
Abstract : Background: : The aim was to compare serum soluble urokinase‐type plasminogen activator receptor (suPAR) levels as well as interleukin‐6 levels (IL‐6) in pregnant women with hyperemesis gravidarum (HG) and asymptomatic pregnant women. Methods: : Our study population consists of voluntary first trimester‐pregnant women who applied to the outpatient clinic of the department of obstetrics and gynecology of Ankara Ataturk Training and Research Hospital. Between February and May 2016, 60 pregnant women were included in our prospective study. Serum suPAR and IL‐6 levels were evaluated with the ELISA method. Twenty‐nine pregnant women with HG and 31 asymptomatic pregnant women were included in the study. Results: : Serum suPAR level in the HG group was measured as 0.36 ± 0.56 ng/ml, whereas this level in the healthy pregnant control group was measured as 0.15 ± 0.15 ng/ml ( p < 0.05). The interleukin‐6 level in the HG group was 5.69 ± 2.16 pg/ml, whereas in the control group it was measured as 3.88 ± 0.28 pg/ml ( p < 0.05). Conclusion: : Serum suPAR and IL‐6 levels proved to be high in the HG group. It is likely that suPAR could play a role in the etiopathogenesis of hyperemesis gravidarum.